Complex refractive index of secondary organic aerosol generated from isoprene/NOx photooxidation in the presence and absence of SO2. Issue 15 (10th August 2015) - Nakayama, Tomoki; Sato, Kei; Tsuge, Masashi; Imamura, Takashi; Matsumi, Yutaka
Abstract: We report the first measurements of the complex refractive index (RI) at 375, 405, 532, and 781 nm for secondary organic aerosol (SOA) generated from isoprene/NOx photooxidation. At all wavelengths studied, slightly greater real components of the RI were observed for the SOA generated in the absence of SO2 compared with those generated in its presence. Considering the chemical properties, the differences in the oxidation state and/or ratio of particle density to molecular weight of compounds in the SOA are considered to be the main factors determining the real components. The imaginary components at ≤532 nm were found to increase with increasing initial SO2 concentration. The highly conjugated oligomers are suggested to be plausible chromophore candidates. This study suggests that when large amounts of SOA are generated after mixing of isoprene with NOx and SOx, light absorption of these SOAs may compete with that of black carbon, especially at ultraviolet wavelengths. Key Points: Complex refractive index ( m = n − ki ) of the isoprene SOA is determined Larger n values are obtained in the absence of SO2 than in the presence of SO2 Significant k values at 375, 405, and 532 nm are observed in the presence of SO2